Evaluation of dose distributions in the overlapping regions of the modulated volumetric arcs used in total body irradiation in pediatric patients - Carrasco Solis, Eduardo; A. Anticona Verástegui, Antonella; Márquez Pachas, J. Fernando; Gonzales-Ccoscco, Alberto E.; Querebalu Garcia, Cecilia; Miranda Tunque, Yesenia; Sarria Bardales, Gustavo; Herrera Castillo, Carlos; Artemio Meca Castro, Edward; Santa Cruz Delgado, José; Carrasco, Fernando; Perini, Ana; et al. (Reports of practical oncology and radiotherapy, 2025)
The application of total body irradiation (TBI), using intensity-modulated techniques with dynamic arcs, creates overlap at the treatment arc boundaries, which can lead to dosimetric variations. Therefore, this research aimed to evaluate the dose distributions in the overlap regions of the arcs used in total body irradiation in pediatric patients. This dosimetric evaluation was conducted on a CIRS 715-TY0710 pediatric body simulator, where a treatment plan with three isocenters was designed, generating two 4 cm overlap regions along the line connecting the isocenters. The plan was verified using the gamma criteria of 3%/3mm and 5%/5mm with the Octavius 4D software. The planning results showed 98.2% dose coverage over 95% of the planning target volume (PTV) with adequate tolerance for risk organs. Regarding the gamma analysis, the acceptance rate was greater than 95% at the treatment isocenters with criteria of 3%/3 mm and 5%/5 mm. However, there is a decrease in the approved points in the overlap zone when evaluated with a 3%/3 mm criterion, while maintaining an approval percentage above 95% when evaluated with a 5%/5 mm criterion.